Global Internet Governance: Russian Approach and International Practice - E. S. Zinovieva (Vestnik MGIMO-Universiteta)
The article studies the processes of Internet governance at the international level in the context of the position and interests of Russia in this area. The theory of global governance was used as a theoretical and methodological framework of the study. Initially, Internet governance was carried out on the state level, with coordination carried out in the interests of the United States created the Internet. At the present stage states and other actors in world politics has to be integrated into the existing system of Internet governance, resulting in development of multi-level or multi-directional diplomacy, formation of the so-called "hybrid" organizations and new models of cooperation. There are new formats of regulation of international relations formed under the influence of scientific and technological progress. Russia's position on Internet governance is based on the goal to ensure equal consideration of interests of all states in the governance of the Internet.